2014
DOI: 10.1016/j.neuroscience.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal betamethasone does not affect glutamatergic or GABAergic neurogenesis in preterm newborns

Abstract: Prenatal glucocorticoids (GCs) are routinely used for pregnant women in preterm labor to prevent respiratory distress syndrome and intraventricular hemorrhage in premature infants. However, the effect of antenatal GCs on neurogenesis in preterm neonates remains elusive. Herein, we hypothesized that prenatal GCs might suppress both glutamatergic and GABAergic neurogenesis in preterm rabbits and that this treatment would induce distinct changes in the expression of transcription factors regulating these developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Betnovate solution -Scalp application 30 ml -Betamethasone 0.1% w/w (as Betamethasone Valerate) was topically applied on shaving area of back skin (5  5), for 2 months according to Vose et al (2014).…”
Section: Application Of Medicationmentioning
confidence: 99%
“…Betnovate solution -Scalp application 30 ml -Betamethasone 0.1% w/w (as Betamethasone Valerate) was topically applied on shaving area of back skin (5  5), for 2 months according to Vose et al (2014).…”
Section: Application Of Medicationmentioning
confidence: 99%
“…Betnovate solution -Scalp application 30ml -Betamethasone 0.1% w/w (as Betamethasone Valerate) was topically applied on shaving area of back skin (55), for 2 months according to Vose et al (2014).…”
Section: Application Of Medicationmentioning
confidence: 99%
“…Despite this finding in the guinea pig placenta, in humans exposure to a single course of betamethasone is not associated with an alteration in the neurosteroid synthesis enzymes 5α-reductase type 1 and 2 in the placenta ( 83 ), presumably due to the repeated vs. single course administration. Additionally, a study in rabbits using a single course of betamethasone based on the recommended human dose revealed no adverse effects of betamethasone on GABAergic and glutamatergic neurogenesis ( 84 ). However, a recent population-based retrospective cohort study in Finland has identified a significant increase in behavioral disorders in children that were exposed to a single course of betamethasone in utero ( 85 ).…”
Section: Role Of Environmental Insults In Failure Of Oligodendrocytesmentioning
confidence: 99%